Hubungan Usia dan Pekerjaan dengan Keluhan Muskuloskeletal pada Ibu Rumah Tangga di Desa Bedali - Fiqih Sabna Ruka; Mohamad Rais Arsyad Al Banjari; Tabhita Chaerunissa At Thariq; Kurniani Fatma Hardini (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Musculoskeletal disorders (MSDs) are major health problems that affect an individual's quality of life by resulting in physical disability and chronic pain. This study aims to measure the accuracy of age and additional work as independent risk factors for musculoskeletal complaints among housewives in Bedali Village, Ngancar District, Kediri Regency. This research is a quantitative explanatory research using a survey method on 20 housewives aged 26-35 years, with data collection through interviews and questionnaires. Data analysis used the Spearman correlation coefficient test with the results being said to have a very weak relationship (p = 0.00 – 0.25), quite strong (p = 0.26 – 0.5), strong (p = 0.51 – 0, 75), and very strong (p = 0.76 – 0.99). The results showed that there was no significant correlation between age and musculoskeletal complaints (p=-0.05), however, a correlation was found with additional work (p=0.875). Based on these findings, it is recommended that health promoters shift their focus from indicators that only focus on elderly people to communities with high workloads to reduce the risk of disability due to MSDs.